CROSS-COUNTRY MANGROVE CONSERVATION: SYNERGY OF PUI MANGROVE USU AND PUI UNPRI SPATIAL DEVELOPMENT IN THE 3RD SUMMER COURSE IN LANGKAT - Robert Tua Siregar; Ira Modifa; Puji Syukran; Despaleri Perangin-Angin (RADJA PUBLIKA, 2025)
Mangrove ecosystems have a crucial role as coastal fortresses as well as supporting the ecological and economic balance of the community. As a tangible manifestation of the implementation of the Tri Dharma of Higher Education, the Center for Excellence in Science and Technology (PUI) of the University of North Sumatra in synergy with Universitas Prima Indonesia held a 3rd Summer Course with the theme